Manfaat Proloterapi pada Osteoartritis Lutut - Deeng, Gracia V. Y.; Sekeon, Sekplin A. S.; Warouw, Finny (Universitas Sam Ratulangi, 2021)
Abstract: Osteoarthritis (OA) is calcification of the joint associated with severe painful sensation caused by joint instability. This joint instability is affected by destruction of cartilage that protects the bones. Osteoarthritis can be caused by various factors such as age, genetic as well as vigorous exercise or activity. As the cartilage destruction progresses, the unprotected bone will rub on the other bone in the joint which can lead to osteoarthritis. Management of OA consists of a variety of treatments, such as pharmacological, non-pharmacological, non-pharmacotherapy, and surgery treatments. Due to the development of science and technology, various modalities have emerged that can support the treatment of OA inter alia prolotherapy. Prolotherapy or regenerative injection could influence the recovery of the destructed area directly and relief the painful sensation through the actions of inflammatory cells, macrophages, immune cells, and cytokines, therefore, the improvement of the destructed areas could occur faster. It was reported that knee osteoarthritis could be treated with prolotherapy successfully. In conclusion, since prolotherapy influences the body to repair the destructed areas, hence it could be used as the new osteoarthritis treatment, especially knee osteoarthritis.Keywords: prolotherapy, knee osteoarthritis, chronic painÂ Abstrak: Osteoartritis (OA) merupakan pengapuran sendi yang disertai nyeri hebat, disebabkan oleh karena adanya ketidakstabilan sendi yang dipengaruhi oleh rusaknya tulang rawan yang berperan untuk melindungi tulang. Osteoartritis dapat disebabkan oleh berbagai faktor seperti usia, jenis kelamin, genetik, aktivitas maupun olahraga berat. Saat tulang rawan rusak, maka tulang yang tidak dilindungi dapat saling bersinggungan di sendi sehingga sendi hancur dan berujung pada OA. Pengobatan untuk OA terdiri dari beragam pengobatan baik farmakologi, non-farmakologi, non-farmakoterapi, maupun tindakan operasi. Seiring berjalannya perkembangan ilmu pengetahuan dan teknologi, maka muncul berbagai modalitas yang dapat menunjang pengobatan OA, antara lain proloterapi. Proloterapi atau injeksi regeneratif memengaruhi dan memberi dampak penyembuhan secara langsung pada area yang mengalami cedera maupun nyeri melalui kerja sel-sel radang, makrofag, sel-sel imun, dan sitokin sehingga dapat bekerja lebih cepat untuk perbaikan daerah yang cedera. Telah dilaporkan hasil bermakna dalam peng-gunaan proloterapi pada osteoartritis lutut. Simpulan penelitian ini ialah proloterapi merangsang tubuh untuk memperbaiki daerah yang cedera sehingga merupakan solusi terbaik yang dibutuhkan dalam pengobatan OA dewasa ini terutama pada OA lutut.Kata kunci: proloterapi, osteoartritis lutut, nyeri kronik